CHAPERONIN 20 mediates iron superoxide dismutase (FeSOD) activity independent of its co‐chaperonin role in Arabidopsis chloroplasts. Issue 1 (11th October 2012) - Kuo, W. Y.; Huang, C. H.; Liu, A. C.; Cheng, C. P.; Li, S. H.; Chang, W. C.; Weiss, C.; Azem, A.; Jinn, T. L.
Summary: Iron superoxide dismutases (FeSODs; FSDs) are primary antioxidant enzymes in Arabidopsis thaliana chloroplasts. The stromal FSD1 conferred the only detectable FeSOD activity, whereas the thylakoid membrane‐ and nucleoid‐co‐localized FSD2 and FSD3 double mutant showed arrested chloroplast development. FeSOD requires cofactor Fe for its activity, but its mechanism of activation is unclear. We used reversed‐phase high‐performance liquid chromatography (HPLC), gel filtration chromatography, LC‐MS/MS, protoplast transient expression and virus‐induced gene silencing (VIGS) analyses to identify and characterize a factor involved in FeSOD activation. We identified the chloroplast‐localized co‐chaperonin CHAPERONIN 20 (CPN20) as a mediator of FeSOD activation by direct interaction. The relationship between CPN20 and FeSOD was confirmed by in vitro experiments showing that CPN20 alone could enhance FSD1, FSD2 and FSD3 activity. The in vivo results showed that CPN20‐ overexpressing mutants and mutants with defective co‐chaperonin activity increased FSD1 activity, without changing the chaperonin CPN60 protein level, and VIGS‐induced downregulation of CPN20 also led to decreased FeSOD activity. Our findings reveal that CPN20 can mediate FeSOD activation in chloroplasts, a role independent of its known function in the chaperonin system.